INSTITUTIONAL DETERMINANTS OF ZAKAT PAYMENT DECISIONS: THE MEDIATING ROLE OF FAMILY FINANCIAL PLANNING - Eko Muliansyah; Muh Gani Irwansyah (Jurnal Education and Development, 2026)
This study examines the role of institutional determinants—namely accountability, transparency, and operational efficiency—in shaping zakat payment decisions, with family financial planning serving as a mediating variable. Drawing on an institutional and household financial behavior perspective, the study investigates how the quality of zakat institution governance influences individual decisions to fulfill zakat obligations. The research employs a quantitative approach using survey data collected from 399 respondents, selected through a non-probability sampling technique from a population of 105,644 potential zakat payers. Data were gathered through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that accountability, transparency, and operational efficiency have a positive and significant effect on zakat payment decisions. Moreover, family financial planning is found to play a significant mediating role in strengthening the relationship between institutional determinants and zakat payment decisions. These results indicate that effective institutional governance not only directly enhances trust and compliance but also indirectly influences zakat payment behavior by encouraging better household financial planning. This study contributes to the literature on zakat governance and Islamic financial behavior by highlighting the importance of integrating institutional performance with household financial planning mechanisms to improve zakat participation. The findings provide practical implications for zakat institutions in designing governance strategies that foster sustainable zakat compliance.